Eritoran attenuates tissue damage and inflammation in hemorrhagic shock/trauma - Korff, Sebastian; Loughran, Patricia; Cai, Chanchun; Lee, Yi Shan; Scott, Melanie; Billiar, Timothy R. (Journal of surgical research, 2013)
Background - Severe injury and associated hemorrhagic shock lead to an inflammatory response and subsequent increased tissue damage. Numerous reports have shown that injury-induced inflammation and the associated end-organ damage is driven by Toll-like receptor 4 (TLR4) activation via damage-associated molecular patterns. We examined the effectiveness of Eritoran tetrasodium (E5564), an inhibitor of TLR4 function, in reducing inflammation induced during hemorrhagic shock with resuscitation (HS/R) or after peripheral tissue injury (bilateral femur fracture, BFF). - Material and methods - Mice underwent HS/R or BFF with or without injection of Eritoran (5 mg/kg body weight) or vehicle control given before, both before and after, or only after HS/R or BFF. Mice were sacrificed after 6 h and plasma and tissue cytokines, liver damage (histology; aspartate aminotransferase/alanine aminotransferase), and inflammation (NF-κB) and gut permeability were assessed. - Results - In HS/R Eritoran significantly reduced liver damage (values ± SEM: alanine aminotransferase 9910 ± 3680 U/L versus 1239 ± 327 U/L and aspartate aminotransferase 5863 ± 2000 U/L versus 1246 ± 243 U/L, P < 0.01) at 6 h compared with control when given just before HS and again just prior to resuscitation. Eritoran administration also led to lower IL-6 levels in plasma and liver and less NF-κB activation in liver. Increases in gut barrier permeability induced by HS/R were also prevented with Eritoran. Eritoran similarly diminished BFF-mediated systemic inflammatory responses. - Conclusion - These data suggest Eritoran can inhibit tissue damage and inflammation induced via TLR4/myeloid differentiation factor 2 signaling from damage-associated molecular patterns released during HS/R or BFF. Eritoran may represent a promising therapeutic for trauma patients to prevent multiple organ failure.
Gesehen am 01.12.2021